Islamic School Leadership Model: The Challenge in Digital Era - Muhammad Thohri (STAI Hubbulwathan Duri, 2022)
This study aims to obtain a leadership model in Islamic schools in the digital era. The principal's leadership must be able to face today's global challenges and be by the character of Islamic schools. The gap in this study related to the role of the leader is very influential on the sustainability of all activities in school institutions, and the needs of the current context provide different demands. The research method uses descriptive qualitative through surveys. Data collection techniques using observation and interviews. The research was conducted in 5 Islamic elementary schools in Ampenan Mataram District. Data analysis uses three stages, namely 1) the reduction stage is carried out by the process of data categorization and data collection. 2) The stage of presenting data, articles and observations that have been obtained is entered into a work table that has been prepared and then analyzed. 3) The conclusion drawing stage is carried out after the data analysis process is complete. The results of the study indicate that the leadership model in Madrasah Ibtidaiyah in the digital era has a character that is quite by the needs in the context of globalization. The leadership characteristics possessed are transformative, managerial, collaborative, democratic, participatory, upholding morals and religious values. Leadership is also open to various changes in science and technology so that schools lead schools according to the context of the needs of the global era and digital technology